Apropriação econômica da religião e a política de desenvolvimento do turismo: reflexões a partir do Memorial Frei Damião, Guarabira-PB - Araujo, Leandro de Pontes (2013)
This study aims to explore the relationships linking the production and consumption of tourism products , from the cultural and political context of its creation until the reverberations , linked to practical production of space . In this sense , this paper proposes a discussion about the " capitalist production of space " , reflecting on the existence and conflicts between public policies linked to tourism in the municipality of Guarabira , Paraíba . The reflection on the actions of policy planning or administrative operations and its spatialization in the city , served as the spatial area for the analysis of the subject . In Guarabira in Paraíba arid , religious Frei Damiao has become the religion of popular character icon, attracting large crowds who attended his sermons missionaries , coming from neighboring cities and states . The Memorial Frei Damiao , main material artifact that characterizes the production of contemporary space of the city facing the commercialization of the religious phenomenon , is recognized by public managers , the administrative policies and by local society , as a " symbol Catholic faith in the state of Paraíba " . The research hypothesized that the production of space in the municipality in question was the scene of social and political factors that led to the election of the city as a place of religious tourism in the arid zone of the state of Paraiba , where capitalist restructuring processes , gave up the uneven and combined. Tourism is a complex phenomenon that contributed to the reconstruction of society , from the actions of the actors involved in the process , building the material dimension and symbolic dimension . The research undertaken so far helped analyze the phenomenon of religious tourism from the point of view of interaction with the material and symbolic magnitudes of the reality of the city of Guarabira . Thus , one has to analyze the capitalist production of space from the economic appropriation of religion, population dynamics seen in the city of Guarabira and influence linked to tourism practice in that county policy , identifying the main actions promoted by government for local development that have collaborated and / or not to the production of space . The present work has the following problem : What is the influence of public policy on tourism development for the production of space in the city of Guarabira ? The spatial structure of the study is on the socioeconomic context and the actions implemented in the municipality of Guarabira , collaborating with the production of space and the correlation with the economic appropriation of religion . Where diversity of actors construct reality from different interpretations , establishing relations of cooperation and conflict in relation to the interests involved . In this sense, it seems timely to reflect that the practice of religious tourism in the municipality of Guarabira figure as a potential not as a vocation , ie , something that was created , not something that has been inherited.